"INTRA UMMAH TRADE" And Its Role In The Stability Of Muslim Countries - Zabih Ullah Yousafzai (Journal of Law, Social Science, and Management Review, 2026)
One of the main development required for the prosperity of humans in the world is economic development. Enhancing economy in turn requires trade. For the Muslim world to put up with all the other countries of the world while also bearing the Islamic principles, the most feasible option is trade with other Muslim countries. In the paper we will be concerned with several benefits of Intra Ummah trade. The article will examine the importance of intra ummah trade for stability of Muslim countries, Current situation of intra ummah trade in light of facts and figures, Possibilities of intra ummah trade in current era. Intra ummah trade assumes for Muslim countries to enhance their domestic productivity and efficacy in the international forums. It will also protect them from external economic exploitation but there may be external challenges for Muslims countries in business world. Which will be face up by beauty of tolerance and patient.